The rise and fall of moral conflicts in the United States and Canada - Schwartz, Mildred A., 1932-; Tatalovich, Raymond (University of Toronto Press, 2017)
"In The Rise and Fall of Moral Conflicts in the United States and Canada, sociologist Mildred A. Schwartz and political scientist Raymond Tatalovich bring their disciplinary insights to the study of moral issues. Beginning with prohibition, Schwartz and Tatalovich trace the phases of its evolution from emergence, establishment, decline and resurgence, to resolution. Prohibition's life history generates a series of hypotheses about how passage through each of the phases affected subsequent developments and how these were shaped by the political institutions and social character of the United States and Canada. Using the history of prohibition in North America as a point of reference, the authors move on to address the anticipated progression and possible resolution of six contemporary moral issues: abortion, capital punishment, gun control, marijuana, pornography, and same-sex relations. Schwartz and Tatalovich build a new theoretical approach by drawing on scholarship on agenda-setting, mass media, social movements, and social problems. The Rise and Fall of Moral Conflicts provides new insights into how moral conflicts develop and interact with their social and political environment."--